Bis-substituted diphenylamine arylidene hydrazones for the synthesis of new binuclear organotin(IV) complexes: Crystal structure, DNA cleavage and molecular docking. (15th November 2018) - Yousefi, Maryam; Sedaghat, Tahereh; Simpson, Jim; Motamedi, Hossein; Dayer, Mohammad Reza
Graphical abstract: Five new dinuclear organotin(IV) complexes have been synthesized and investigated by spectral methods and X-ray crystallography. Biological activity and molecular docking of ligands and complexes have been also investigated. Abstract: Five dinuclear organotin(IV) complexes, R4 Sn2 L a (R = Me, Ph) and R4 Sn2 L b (R = Me, Ph and Bu) have been synthesized from reaction of R2 SnCl2 with 2, 4′- and 2, 2′-bis-substituted diphenylamine arylidene hydrazones, H4 L a and H4 L b, respectively. The synthesized compounds have been investigated by elemental analysis and IR, 1 H NMR, and 119 Sn NMR spectroscopy. The structures of Me4 Sn2 L b and Ph4 Sn2 L b have been also confirmed by X-ray crystallography. The results show that the fully deprotonated bis-hydrazone ligand provides two contiguous ONO tridentate domains that coordinate to the two SnR2 moieties in the enolate form. Each tin atom in the complexes adopts a five-coordinate environment. Ligands and complexes showed no antibacterial activity against Gram-positive ( Bacillus subtilis and Staphylococcus aureus ) and Gram-negative ( Escherichia coli and Pseudomonas aeruginosa ) bacteria. However, both ligands and their methyl complexes were found to degrade DNA, an observation that adapt with the mode of interaction suggested by molecular docking.